2015
DOI: 10.1177/0278364914558016
|View full text |Cite
|
Sign up to set email alerts
|

Compliance in parallel to actuators for improving stability of robotic hands during grasping and manipulation

Abstract: Humans exploit the inherent biomechanical compliance in their fingers to achieve stability and dexterity during many manipulation tasks. The compliance is a result of muscles and tendons (series compliance) and flexible joints (parallel compliance). While the effects of series compliance have been studied in many robotic systems, research on the effects of joint compliance arranged in parallel with the actuators is limited. In this paper, we first demonstrate, through mathematical modeling, that introducing pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…The maximum muscle force is normalized, and then, according to Equations (1)-( 8), the schematic diagram of the muscle force composition (muscle activation degree is 1), as shown in Figure 2, can be obtained. The parameters in the Hill muscle model are obtained according to the research by Thelen and Holzbaur [17,29].…”
Section: Muscle Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The maximum muscle force is normalized, and then, according to Equations (1)-( 8), the schematic diagram of the muscle force composition (muscle activation degree is 1), as shown in Figure 2, can be obtained. The parameters in the Hill muscle model are obtained according to the research by Thelen and Holzbaur [17,29].…”
Section: Muscle Modelmentioning
confidence: 99%
“…A CE is the core element of the Hill muscle model, and it can produce active muscle contraction [15]. According to the structural similarity of the Hill muscle model, researchers have designed various elastic actuators, which are mainly divided into series elastic actuators (SEAs) [16], parallel elastic actuators (PEAs) [17], clutchable elastic actuators (CEAs), and multi-configuration elastic actuator (MEAs) [18,19]. In terms of the transmission mode, elastic actuators can be divided into rotary types and linear types.…”
Section: Introductionmentioning
confidence: 99%
“…Series elastic actuation (SEA) can simplify control, improve robustness and interaction safety, and protect actuators from overloads ( Raibert et al, 1984 ; Robinson et al, 1999 ; Pratt and Krupp, 2004 ; Hutter et al, 2011 ; Calanca et al, 2015 ; Hutter et al, 2016 ; AhmadSharbafi et al, 2020 ). Designs with parallel mounted springs and actuators (parallel elastic actuation, PEA) can increase leg forces, improve locomotion energy efficiency, and reduce actuator loading ( Gunther et al, 2015 ; Niehues et al, 2015 ; Plooij et al, 2016 ; Yesilevskiy et al, 2016 ; Liu et al, 2018 ; Toxiri et al, 2018 ; Yesilevskiy et al, 2018 ; Roozing et al, 2019 ; Ambrose and Ames, 2020 ). Combined parallel and serial elastic designs have been proposed, leading to reduced peak torques and improved locomotion applicability ( Grimmer et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Such design and development were mainly achieved through the construction of compliant actuators [29,30,31] and the introduction of stiffness variable joints [32,33]. It has been shown that robotic hand with variable stiffness or compliance could improve stability and simplify control during grasp and manipulation [34,35]. However, mechanical compliance realized through the transmission systems in robotic design has rarely been reported.…”
Section: Introductionmentioning
confidence: 99%